Analisis Kinerja Keuangan Daerah dan Pengaruhnya Terhadap Pertumbuhan Ekonomi Provinsi Jambi Tahun 1998-2017 - Deby Anggun Sari (JUMANJI (JURNAL MANAJEMEN JAMBI), 2021)
This study aims to analyze the development of regional financial performance and analyze the effect of the regional financial performance of Jambi Province on economic growth before and after regional autonomy. The data used in this empirical study is a secondary data series from 1998 to 2017 originating from the Central Statistics Agency. (BPS) and the Regional Finance Agency of Jambi Province. The analytical method used in this study is descriptive and quantitative analysis. The results of the study explain the existence of a positive and significant relationship between regional independence variables with economic growth variables in Jambi Province. Then, the existence of a negative relationship and significant influence of regional dependence and fiscal decentralization on economic growth The results of the study during the period before the implementation of the regional autonomy policy can be concluded that all independent variables together influence the dependent variable (economic growth). During the period before the implementation of regional autonomy, there were no variables individually which had a significant effect on regional economic growth in the study area. This can be seen from each variable that is not significant at the 5 percent significance level. Then, there are differences in government financial performance in aspects of fiscal efforts after regional expansion, and there are differences in government financial performance in aspects of independence and dependence on financing after regional expansion.